2009
DOI: 10.1098/rstb.2008.0285
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary significance of phenotypic accommodation in novel environments: an empirical test of the Baldwin effect

Abstract: When faced with changing environments, organisms rapidly mount physiological and behavioural responses, accommodating new environmental inputs in their functioning. The ubiquity of this process contrasts with our ignorance of its evolutionary significance: whereas within-generation accommodation of novel external inputs has clear fitness consequences, current evolutionary theory cannot easily link functional importance and inheritance of novel accommodations. One hundred and twelve years ago, J. M. Baldwin, H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(129 citation statements)
references
References 97 publications
(130 reference statements)
3
125
0
1
Order By: Relevance
“…For example, phenotypic plasticity and non-genetic inheritance contributed to the adaptation of the house finch to cold climates during its North American range expansion ( [68]; see [27,28,49,101,105,107] for further examples). The EES also anticipates that variants with large phenotypic effect can occur, for example, through mutations in major regulatory control genes (although most such mutations will still be neutral or deleterious) that can be expressed in a tissue-or module-specific manner (e.g.…”
Section: (B) Reciprocal Causationmentioning
confidence: 99%
“…For example, phenotypic plasticity and non-genetic inheritance contributed to the adaptation of the house finch to cold climates during its North American range expansion ( [68]; see [27,28,49,101,105,107] for further examples). The EES also anticipates that variants with large phenotypic effect can occur, for example, through mutations in major regulatory control genes (although most such mutations will still be neutral or deleterious) that can be expressed in a tissue-or module-specific manner (e.g.…”
Section: (B) Reciprocal Causationmentioning
confidence: 99%
“…A major impediment to testing this prediction is that ancestral populations are usually no longer available for study, making it difficult to characterize ancestral reaction norms. The best systems for testing this prediction are therefore those in which ancestral populations are extant [28][29][30]. Below, we describe several studies in which genetic accommodation has been inferred in natural populations.…”
Section: (C) Genetic Accommodation In Natural Populationsmentioning
confidence: 99%
“…However, while the idea of the Baldwin effect is more than 100 years old and many studies have demonstrated how organisms rapidly respond both physiologically and behaviourally to changing environments, we still cannot easily link functional importance and inheritance of novel accommodations, i.e. the idea that natural selection sorts among developmental variants for genes enabling plasticity and flexibility [78]. In other words: we do not know whether flexible genes versus inflexible genes exist (but see [79]).…”
Section: Physiological Mechanisms Underlying Intraspecific Variation mentioning
confidence: 99%